TABUNGAN: IMPLEMENTASI AKAD WADI’AH ATAU QARD? (Kajian Praktik Wadi’ah di Perbankan Indonesia) - Mufti Afif (Jurnal Hukum Islam, 2014)
There are no discussion about banking usury in classic Fikh books, because there were no banks, which nowadays they are needed by society to save their worth. As the research of classic Fiqh, there are differences in ulamas’ instructions, based on their understanding. However, they agree to state that bank interest is a usury or forbidden in Islam. Qardul Hasan is another term of qard, that is interpreted by the most of Indonesian people as social engagement, or bequest. Financial department must be careful in understanding the instructions, related to the implementation in the real life. Banks and financial departments claim that money saving is as akad wadi’ah yad dhamanah, whereas the meaning of dhomanah is responsibility. Fiqh ulamas decide that actually, wadi’ah is responsible. Yad dhamanah is irresponsible.